(untitled) (Journal of Informatics Education and Research, 2025)
Objective: This research examines how leadership styles affect teacher migration in international private schools through the investigation of leadership’s influence on retention and mobility factors. This study explores leader effectiveness through measurements which relate to teacher satisfaction while focusing on leadership improvement strategies for increased teacher retention.